OYO: The Rise and Fall of Oyo’s Marketing Communication: A study on the marketing communication strategies and business model of OYO (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This study is providing theoretical and conceptual base for one of the already established service firm OYO’s brand, their business model and Marketing communication strategies. The data collected for the study from their official websites and other published secondary sources. This study proposes the recommendations in two way present and post-covid scenario.